Komunikasi Transendental Ritual Keagamaan Tarekat Qadiriyyah wa Naqsabandiyyah Pesantren Suryalaya Tasikmalaya - Enjang AS; Ridwan Rustandi (Program Studi Ilmu Komunikasi, 2022)
This study aimed to analyze transcendental communication in TQN religious rituals at Pesantren Suryalaya Tasikmalaya. The research was conducted with a constructivist paradigm and a qualitative approach. Data collection was carried out through observations, interviews, documentations, and literature study. The results of the study concluded that the source of transcendental communication messages came from theological (Al-Quran), prophetic (Al-Hadith), and authority (TQN principles, Tanbih manuscripts, and strands of pearl) messages that acted as wills, advices, and teachings from Abah Anom. By using the Lasswell communication model, it was found that the main communicators in this transcendental communication process were sheiks, murshids, and talqin guardians. The communication messages were the TQN principles, the Tanbih scriptures, and the Pearl Strand. The medium of communication were the uqudul juuman and distinctive practice based on the teachings of TQN. The communicants were TQN students, TQN congregations, students of educational institutions, and the general public. The feedback was in the form of practices which aimed at tazkiyatu an-nafs, taqarrub, mardhatillah, mahabbah, and makrifat